2022
DOI: 10.1016/j.cmi.2021.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive diagnosis of Pneumocystis jirovecii pneumonia: a systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 67 publications
2
12
0
Order By: Relevance
“…According to PCR positive, 4 cases of PJP were proven, among these,one was heart transplant, one was HIV infection, others were taking prednisone (data were not shown). BALF PCR had a sensitivity of 100% in our study, this value is similar to those reported at 99% [28] and 98%. [29] This study found that serum GM test for the detection of yeast infection has a sensitivity of 50% and a fairly low PPV of 35.7%, partly because the subject enrolled are non-neutropenic patients with COPD.…”
Section: Discussionsupporting
confidence: 91%
“…According to PCR positive, 4 cases of PJP were proven, among these,one was heart transplant, one was HIV infection, others were taking prednisone (data were not shown). BALF PCR had a sensitivity of 100% in our study, this value is similar to those reported at 99% [28] and 98%. [29] This study found that serum GM test for the detection of yeast infection has a sensitivity of 50% and a fairly low PPV of 35.7%, partly because the subject enrolled are non-neutropenic patients with COPD.…”
Section: Discussionsupporting
confidence: 91%
“…Despite being simple and inexpensive, traditional microscopic examination is less sensitive for PJP because of the low fungal load. Despite having 100% specificity for the diagnosis of PJP, immunofluorescence and cytological staining only exhibited a 74% and 50% sensitivity, respectively, according to a meta-analysis ( Senécal et al, 2022 ). In this study, PJ was detected among alveolar lavage fluid in only two children due to the limited sensitivity of the conventional assay.…”
Section: Discussionmentioning
confidence: 99%
“…Second, most of the PLWH who were included in our study used sputum or gargling specimens to detect P. jirovecii with the use of PCR assays. In a meta-analysis, minimally invasive PCP diagnostic tests that used induced sputum and oral wash showed good specificities in PLWH (98% and 95%, respectively) ( 38 ); however, the oral wash specimens had a lower sensitivity (74%). Therefore, the diagnosis of PCP in our study might have been underestimated.…”
Section: Discussionmentioning
confidence: 99%